Implementation of waste cooking oil as RAP rejuvenator - Asli, H.; Karim, M.R. (2011)
In this paper, the implementation of using waste cooking oil as a rejuvenating agent that used in RAP is investigated. The simulation of ageing process is accelerated by unconventional method using propeller mixer, (MIXER) and rolling thin film oven test, (RTFOT). The binder tests are by means of Penetration test, Softening Point test, Brookfield Viscosity test and Dynamic Shear Rheometer, (DSR) test to measure original bitumen, aged bitumen and rejuvenated bitumen properties. It was observed that unconventional method is produced aged bitumen pen-grade of 60/70, 50/60, 40/50 and 30/40 which have penetrations between of 60 to 70, 50 to 60, 40 to 50 and 30 to 40, respectively while RTFOT shown 50/60 aged penetration grade. The results indicate that the aged bitumen is rejuvenated by the waste cooking oil due to change in physical and rheological properties that revived to original bitumen (Fresh Bitumen).